The Use of Role Playing Methods as Ethics Cultivation in the Subject of Aqidah Akhlak for Grade IX Students of MTsN 12 Indramayu - Mahra Alfina; Didik Himmawan (Manajia: Journal of Education and Management, 2025)
This study aims to describe the form of use of the role playing method as an instillation of ethics in the subject of faith and morals and to define and describe the supporting and inhibiting aspects in the use of the role playing method as an instillation of ethics in the subject of faith and morals. This study uses a Classroom Action Research approach. The results of the study indicate that the role of the role playing method seen from the subject of faith and morals can teach ethics about getting to know each other, understanding each other, helping each other, doing good, being honest, fair, trustworthy and keeping promises. The most appropriate way to maintain ethics is to play a role. The results of this study can motivate parents, teachers or guardians to always provide role-playing games to children so that the instillation of ethics can increase.